Microalgae bioreactor for nutrient removal and resource recovery from wastewater in the paradigm of circular economy. (November 2022) - Díaz, Verónica; Leyva-Díaz, Juan Carlos; Almécija, Mari Carmen; Poyatos, José Manuel; del Mar Muñío, María; Martín-Pascual, Jaime
Graphical abstract: Highlights: A new compound anti-stripping additive called DMA-NSDD was developed. The asphalt and its mixture performance was investigated by experiments. A comparison was made of the performance of seven asphalts and their mixtures. The performance of asphalt with DMA-NSDD and its mixtures was markedly improved. Abstract: Every day, large quantities of wastewater are discharged from various sources that could be reused. Wastewater contains nutrients such as nitrogen or phosphorus, which can be recovered. Microalgae-based technologies have attracted attention in this sector, as they are able to bioremediate wastewater, harnessing its nutrients and generating algal biomass useful for different downstream uses, as well as having other advantages. There are multiple species of microalgae capable of growing in wastewater, achieving nutrient removal efficiencies surpassing 70%. On the other hand, microalgae contain lipids that can be extracted for energy recovery in biodiesel. Currently, there are several methods of lipid extraction from microalgae. Other biofuels can also be obtained from microalgae biomass, such as bioethanol, biohydrogen or biogas. This review also provides information on bioenergy products and products in the agri-food industry as well as in the field of human health based on microalgae biomass within the concept of circular bioeconomy.